How Valuable Are Organic Amendments as Tools for the Phytomanagement of Degraded Soils? The Knowns, Known Unknowns, and Unknowns - Gómez-Sagasti, María T.; Hernández, Antonio; Artetxe, Unai; Garbisu, Carlos; Becerril, José M. (Frontiers in Sustainable Food Systems, 2018)
Soils functionality (health) and productivity (quality) are severely impaired by the rapid growth of human population and by the fact that most of the cultivable land is intensively used, whether for urbanization or for meet the food requirements, with the consequent rise in solid and liquid wastes and consumption of agricultural soils. However, these issues, far from being independently handled, can be jointly addressed by an integrated and sustainable management of soil resource in the framework of circular economy and phytomanagement. Currently immersed in resource-conserving and regenerative (urban) land management, three fundamental aspects are looked after together: (i) the valorization and safe recovery of organic wastes (e.g. composts, green and animal manures, and biosolids) as soil amendments to abate their landfilling (from residue to resource); (ii) the re-development of degraded soils, often characterized by low organic matter, deficient physical structure and depressed biological status, to keep pressure off agricultural soils (from bare to vegetated soil), and finally; (iii) the promotion of soils health in order to support soil processes and ecosystem services at long-term (integration of ecological and anthropocentric perspectives). Through this review we renewed attention in the benefits (knows), potential risks (known unknowns) and future/affordable uncertainties (unknowns) resulting from soil application of organic amendments (OAs). Traditionally, most studies have used phycal-chemical parameters to assess soil health/quality, whereas less focus has been given to soil biological properties. We highlight the relevance of soil biological properties -both below and above-ground- as key drivers of soil reclamation and hence as more suitable estimators of soil health. Notwithstanding, special attention should be paid on “amendment-plant-microorganism” tripartite interactions. Using a phytomanagement strategy, here we presented a pilot field study that encompasses the addition of bio-stabilized material resulted from mechanical-biological treatment of Municipal Solid Wastes be used in a peri-urban vacant soils with a dual aim of grow biofuel crops and restore soils health. Our results prove that this phytomanagement approach not only would involve positive environmental synergies but also the return of important economic and social gains to degraded landscapes.